Thinned-out controlled IC MPPT algorithm for class E resonant inverter with PV system - Karafil, Akif (Ain Shams Engineering Journal, 2023)
In this study, maximum power extracted from photovoltaic (PV) panels was transferred to the load using the proposed thinned-out controlled class E resonant inverter. For the system, PV panels were used as a power source. A PV powered system was designed using single switch inverter. Maximum power point tracker (MPPT) controlled resonant inverter was conducted under varying solar irradiation conditions. The output power of the voltage-fed class E resonant inverter circuit was controlled in a wide range by using the thinned-out control method in a fixed switching frequency of 63 kHz. In the proposed method, power control was provided gradually without increasing switching losses significantly by achieving zero voltage switching (ZVS) condition. ZVS conditions were met in most periods when the solar irradiation was at high level and the number of the skipped pulses was low. As a result, soft switching was provided and the single switch inverter could operate with higher efficiency. Incremental conductance (IC) algorithm was used to track maximum power in PV panels and the tracking efficiency was obtained as above 99 % by the proposed novel thinned-out controlled IC MPPT algorithm. The proposed method shows that since electromagnetic interference and switching losses are reduced, the size of the circuit components is also reduced, and therefore there is a significant reduction in the circuit volume and the costs.